Comprehensive multi-factors reveal the pathogenesis of degenerative intervertebral disc - Aikenmu, Kahaer; Wang, Zhenbin; Meng, Qingcai (Cellular and Molecular Biology, 2020)
Intervertebral Disc (IVD) is a moderately moving joint that provides load transfer and flexibility to the entire spine. Although healthy IVD can balance the turnover of slow-synthesis matrices, this balance is often disrupted that leading to the development of degenerative diseases. The pathogenesis and treatment mechanism of Intervertebral Disc Degeneration (IDD) has always been the focus of scientific research, but its pathogenesis is still unknown. Therefore, this study is based on a modular approach to in-depth analysis and explore the genes of IDD, intended to identify the molecular process of disc degeneration. Firstly, the data related to Intervertebral Disc Degeneration and normal intervertebral disc were downloaded from the GEO database. The differential analysis of two kinds of data was performed to obtain differential gene expression profiles. Secondly, mapping those differential genes to Cytoscape to construct protein-protein interaction networks (PPIs). Then, the module gene was subjected to enrichment analysis of GO function and KEGG pathway. Finally, non-coding RNAs (ncRNAs) and transcription factors that regulate the module are predicted based on hypergeometric testing. In summary, we identified 22 co-expression modules, and the enrichment analysis results revealed that the module genes were significantly involved in the regulation of definite biotic procedures. In conclusion, we recognized the ncRNA pivot (including miR-193b-3p, CRNDE, etc.) and TF pivot (including E2F1, E2F4, etc.) that significantly regulate dysfunction modules.